Lactobacillus rhamnosus inhibits Candida albicans virulence factors in vitro and modulates immune system in Galleria mellonella - Ribeiro, F. C. [UNESP]; de Barros, P. P. [UNESP]; Rossoni, R. D. [UNESP]; Junqueira, J. C. [UNESP]; Jorge, A. O.C. [UNESP] (Oxford University Press (OUP), 2017)
Aim: The aim of this study was to evaluate the potential anti-Candida effects of Lactobacillus rhamnosus ATCC 9595 on Candida albicans ATCC 18804 using in vitro and in vivo models. Methods and Results: The in vitro analysis evaluated the effects of L. rhamnosus on C. albicans's biofilm formation by CFU count and metabolic activity, filamentation capacity, and adhesion (ALS3 and HWP1) and transcriptional regulatory gene (BCR1 and CPH1) expression. The in vitro results showed that both the L. rhamnosus cells and supernatant reduced C. albicans biofilm formation, filamentation and gene expression. In the in vivo study, the treatment with L. rhamnosus supernatant increased 80% the survival of Galleria mellonella larvae infected with C. albicans. Furthermore, the supernatant of L. rhamnosus recruited haemocytes into the haemolymph (2·1-fold increase). Conclusions: Lactobacillus rhamnosus reduced the biofilm formation and filamentation of C. albicans in vitro by negatively regulating all studied C. albicans genes. Lactobacillus rhamnosus protected G. mellonella against experimental candidiasis in vivo. Significance and Impact of the Study: This study is the first study to report the anti-Candida properties of L. rhamnosus ATCC 9595. The supernatant of this strain has immunomodulatory effects on the G. mellonella model and protects the larvae against pathogens.
Keywords: biofilms; gene expression; Lactobacillus; probiotics; yeasts